Administrative Challenges and Policy Compliance in the Implementation of Inclusive Education in Indonesian Primary Schools - Diding Bajuri; Lalan Soeherlan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Inclusive education in Indonesia aims to ensure equitable access for all students, including Anak Berkebutuhan Khusus (ABK). However, its implementation in primary schools is often hindered by administrative challenges, affecting schools’ compliance with inclusive education policies. This study employed an explanatory sequential mixed-methods design. In the quantitative phase, surveys were administered to 180 respondents from 30 inclusive primary schools to examine challenges in teacher allocation, lesson planning (RPP), and budget management. Pearson correlation was used to assess the relationship between these challenges and policy compliance. In the qualitative phase, case studies were conducted in three purposively selected schools through interviews and observations. Quantitative findings showed that budget management had the strongest negative correlation with compliance (r = –0.49), followed by RPP management (r = –0.35) and teacher allocation (r = –0.28). Qualitative data revealed that limited funding, lack of professional development, and uneven distribution of support teachers were key barriers. In contrast, proactive leadership and structured internal support systems contributed to higher compliance levels. Administrative constraints significantly influence the ability of schools to meet inclusive education policy requirements. This study highlights the importance of adequate financial resources, professional capacity-building, and equitable staffing in supporting inclusive education. Improving budget allocations, lesson planning support, and teacher deployment is essential to strengthening policy compliance in inclusive primary schools in Indonesia.